The relationships between Perceived Organizational Support, Felt Obligation, Affective Organizational Commitment and Turnover Intention of Academicians Working with Private Higher Educational Institutions in Malaysia - Lew, Tek (Academy of Taiwan Information Systems Research, 2009)
The main objective of this paper is to examine the relationships between perceived organizational support (POS), felt obligation, affective organizational commitment and turnover intention of academicians working for private higher educational institutions in Malaysia. This paper is driven theoretically by the social exchange theory, the concept of perceived organizational support (POS) which is the commitment of the organization to the employee, the norm of reciprocity, the organizational support theory as well as the other relevant literature in the human resource management and organizational behaviour research. This paper contributes to the limited body of knowledge about the psychological processes underlying the formation of organizational commitment through the perspectives of the social exchange theory (Blau, 1964) and the organizational support theory (Eisenberger, et al., 1986; Eisenberger et al., 2001).